(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses one of the most pressing and complex in modern international law and requiring its scientific development - the problem of State responsibility. A very complex issue that arises when considering the issue of liability for environmental damage, is the question of the fault of the state, one of the most controversial in the doctrine of general international law, in particular in international space law.